(untitled) (Perner’s Contacts, 2012)
The paper describing philosophy determination of the coefficient friction flat belt in face of steel tractive disk behind different service conditions. Flat belts are identified above all for maintenance-free application freight and passenger lift, where substitute chains and steel ropes.